At Westonci.ca, we connect you with the best answers from a community of experienced and knowledgeable individuals. Explore our Q&A platform to find reliable answers from a wide range of experts in different fields. Get quick and reliable solutions to your questions from a community of experienced experts on our platform.
Sagot :
The equation of a line is given as:
y = mx + c
Let us get the eqiuations for the first two sets of data points
( 1, 5) and (2, 2)
For (1, 5), the equation becomes:
5 = m + c
m + c = 5........(1)
For (2, 2), the equation becomes:
2 = 2m + c
2m + c = 2........(2)
Subtract equation (1) from (2)
m = -3
Put the value of m into equation (1) to get the value of c
-3 + c = 5
c = 5 + 3
c = 8
The general equation then becomes:
y = -3x + 8
To confirm that this function is right, put the third data point into the equation and see if it is true.
(3, -1)
-1 = -3(3) + 8
-1 = -9 + 8
-1 = -1 (true)
To find the inverse of the function y = -3x + 8
Make x the subject of the formula
-3x = y - 8
[tex]\begin{gathered} \text{x = }\frac{-(y-8)}{3} \\ \text{x = }\frac{-y+8}{3} \end{gathered}[/tex]To get the inverse function, replace x by y, and vice-versa
[tex]y\text{ = }\frac{-x+8}{3}[/tex]We will now use the values of y in the first table as x in the inverse function table:
when x = 5
y = (-5 + 8)/3
y = 3/3, y = 1
When x = 2
y = (-2 + 8)/3 = 6/3
y = 2
When x = -1
y = (-(-1) + 8) / 3 = (1 + 8)/3
y = 9 / 3
y = 3
The table for the inverse function is therefore:
Below is the graph for the original function:Below is the graph for the inverse function:
Thank you for your visit. We're dedicated to helping you find the information you need, whenever you need it. We appreciate your time. Please revisit us for more reliable answers to any questions you may have. We're glad you visited Westonci.ca. Return anytime for updated answers from our knowledgeable team.